Literatur Review : Remote Work Dan Manajemen Karyawan Digital Di Indonesia - Johs Charlos Hutabalia; Jese Marvel Lumban tobing; Michael Saputra Simbolon (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2024)
The purpose of this study is to discuss the impact of remote work on digital employee management, focusing on challenges in work culture, productivity, and HR technology in the hybrid era. With the increasing adoption of hybrid work models, companies need to maintain a positive work culture despite limited social interactions. This study identified that the flexibility of remote work can increase productivity, but also poses a risk of decreased productivity due to lack of effective supervision and communication. Qualitative methods through literature studies and interviews were used to explore employee and manager views. The results showed that managerial support, relevant training, and an inclusive organizational culture are important to overcome these challenges. This study concluded that adaptive and innovative HR management strategies are essential to improve employee productivity and well-being in the digital era.